Detection of porcine circovirus type 3 DNA in serum and semen samples of boars from a German boar stud. (January 2022) - Eddicks, Matthias; Müller, Michael; Fux, Robert; Ritzmann, Mathias; Stadler, Julia
Highlights: Detection of porcine circovirus type 3 (PCV3) in serum was associated with boar age. Detection frequency and viral loads of PCV3 in fresh semen by PCR were low. Boar semen for artificial insemination is likely to be unimportant in PCV3 spread. Abstract: Porcine circovirus type 3 (PCV3) is regularly reported in association with various clinical presentations, including porcine dermatitis and nephropathy syndrome (PDNS)-like lesions, respiratory signs, congenital tremor, and reproductive disorders. To investigate the epidemiology of PCV3 in a boar stud, we analysed fresh boar semen and matching sera from 181 boars from a German stud supplying semen for artificial insemination (AI) to approximately 740 breeder farms for PCV3 DNA. PCV3 DNA was detected in 1.7% semen samples and 24.3% sera. Spearman rho correlation demonstrated a significant positive correlation between boar age and quantitative DNA (by PCR quantification cycles [Cq] values) in serum samples ( r = 0.636; P < 0.001). Sera from boars up to 12 months of age had higher viral loads ( P < 0.001) and were PCV3-positive significantly more often ( P < 0.01) than older boars. Detection of PCV3 DNA was not associated with breed ( P > 0.05). PCV3 DNA was detected sporadically in fresh boar semen. Based on the assumption that processing fresh semen reduces viral load in semen used for AI, it is likely that the risk of sexual transmission of PCV3 during AI in is low. However, young boars may contribute to the maintenance of PCV3 infection in boar studs.